The impact of entrepreneurial education and educational attainment on entrepreneurial activity: evidence from selected high-income economies - Bayar, Yilmaz; Sart, Gamze; Gavriletea, Marius Dan; Coroş, Monica Maria (Journal of Business Economics and Management, 2022)
Entrepreneurship has become an important tool for job creation, economic growth, improvements in productivity and production, and innovation. Therefore, key country and individual-level factors driving entrepreneurship have been explored in the related literature. Furthermore, entrepreneurial education has been extensively scheduled in primary, secondary, and tertiary education programs by many countries. This study explores the impact of entrepreneurial education at primary and secondary education levels, higher education levels, and general education levels on early-stage entrepreneurial activity in selected high-income countries over the period of 2003 to 2018, through panel cointegration and causality analyses. Causality analysis revealed that entrepreneurial education and general education had a significant impact on earlystage entrepreneurial activity in the short run. The cointegration analysis disclosed that both entrepreneurial education at basic and higher education levels, respectively general education level positively affected the early-stage entrepreneurial activity in the long run.